2012
DOI: 10.5539/ies.v6n2p49
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Teachers’ Motivational Indices on Science Students’ Academic Performance in Nigerian Senior Secondary Schools

Abstract: The impact of science teachers' motivation on science students' academic performance in Senior Secondary Schools in Ondo and Ekiti States of Nigeria was investigated in this study. This was a descriptive survey research which was questionnaire based and past WAEC O/L ((May/June 2008 and 2009) student results on the science subjects. The population of the study was all public Secondary Schools (science teachers and students) in Ekiti and Ondo States, Nigeria. A stratified random sampling was used to select a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
(1 reference statement)
2
7
0
Order By: Relevance
“…Motivation is essential in organizational performance and vital for developing educational institutions (Etor & Etudor-Eyo, 2016;Peretemode, 2003). If staff are duly motivated, they will increase their productivity (Oredein & Awodun, 2013). This motivation can come in the form of appreciation of teachers, giving them their salaries on time, ensuring timely promotion and other forms of motivation (McCaffery, 2004).…”
Section: Roles Of Leadership and Higher Education Managers In Reducinmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivation is essential in organizational performance and vital for developing educational institutions (Etor & Etudor-Eyo, 2016;Peretemode, 2003). If staff are duly motivated, they will increase their productivity (Oredein & Awodun, 2013). This motivation can come in the form of appreciation of teachers, giving them their salaries on time, ensuring timely promotion and other forms of motivation (McCaffery, 2004).…”
Section: Roles Of Leadership and Higher Education Managers In Reducinmentioning
confidence: 99%
“…Also, it conforms with the view of Adeyemi and Igbineweka (2000); Babatope (2010) who maintained that facilities must be provided and effectively utilized in order to attain the goals of university education. Furthermore, motivation plays a vital role in teacher's satisfaction, as observed in the study by Oredein and Awodun(2013) who suggested that teachers must be motivated in order to increase their level of productivity. Finally, McCaffery (2004) also suggested that university leaders must be transparent and dynamic in their operation as a way of improving the educational system.…”
Section: Sincerity and Transparencymentioning
confidence: 99%
“…Knowledge of science also develops creativity in its recipients that will lead to self-reliant [4]. Growth of any nation is a degree of its advancement in the area of science and technology respectively [17]. Some developed countries like; Russia, America, Japan, and China to mention few are as a result of the solidity in the area of science and technology.…”
Section: Introductionmentioning
confidence: 99%
“…Some developed countries like; Russia, America, Japan, and China to mention few are as a result of the solidity in the area of science and technology. Science subjects are the base upon which the science and technological advancement of any nation is built [17]. It was reported that Science is the principle upon which the technology is built, without science; there cannot be hunch for technology [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation